2020
DOI: 10.36150/2499-6564-340
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, hospitalisation and sarcopenia among the elderly: a systematic review

Abstract: With the increasing aging population, sarcopenia may become a major issue that requires special attention among healthcare providers. Sarcopenia is a Introduction. Sarcopenia has been demonstrated to affect the quality of life (QoL) of hospitalised elderly. However, no convincing evidence for the best method for measuring sarcopenia in hospitalised elderly is available. The current review aims to investigate the common outcome measures used to measure QoL and sarcopenia in hospitalised elderly. Method. A syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Moreover, the reduction in muscle mass in sarcopenic patients might modify the distribution volumes of hydrophilic drugs, with a higher risk of adverse drug reactions, including druginduced delirium. Of note, elevated blood concentrations of inflammatory cytokines were found in sarcopenic patients, as well as in patients with delirium, suggesting the presence of an inappropriate inflammatory response in both syndromes 17,18 . In particular, some studies reported higher level of C-Reactive Protein (CRP) in patients with sarcopenia without any differences for IL-6 and TNF-a concentration compared to non-sarcopenic patients 17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the reduction in muscle mass in sarcopenic patients might modify the distribution volumes of hydrophilic drugs, with a higher risk of adverse drug reactions, including druginduced delirium. Of note, elevated blood concentrations of inflammatory cytokines were found in sarcopenic patients, as well as in patients with delirium, suggesting the presence of an inappropriate inflammatory response in both syndromes 17,18 . In particular, some studies reported higher level of C-Reactive Protein (CRP) in patients with sarcopenia without any differences for IL-6 and TNF-a concentration compared to non-sarcopenic patients 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, elevated blood concentrations of inflammatory cytokines were found in sarcopenic patients, as well as in patients with delirium, suggesting the presence of an inappropriate inflammatory response in both syndromes 17,18 . In particular, some studies reported higher level of C-Reactive Protein (CRP) in patients with sarcopenia without any differences for IL-6 and TNF-a concentration compared to non-sarcopenic patients 17 . Contrary, in other researches the serum levels of TNF-α were found higher in sarcopenia individuals 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation